2021
DOI: 10.3390/ijerph18179013
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Effects of Payer Restrictions on Reproductive Healthcare: A Qualitative Analysis of Cost-Related Barriers and Their Consequences among U.S. Abortion Seekers on Reddit

Abstract: Objective: The Hyde Amendment and related policies limit or prohibit Medicaid coverage of abortion services in the United States. Most research on cost-related abortion barriers relies on clinic-based samples, but people who desire abortions may never make it to a healthcare center. To examine a novel, pre-abortion population, we analyzed a unique qualitative dataset of posts from Reddit, a widely used social media platform increasingly leveraged by researchers, to assess financial obstacles among anonymous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…There are numerous publications devoted to collecting data from social media, i.e. Reddit (Higgins et al, 2021), Twitter (Hernandez-Suarez et al, 2018; Dongo et al, 2021), Facebook (Mancosu & Vegetti, 2020). There are even manuals concerning scraping data from the web and social media and using it in analytics (Russell, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous publications devoted to collecting data from social media, i.e. Reddit (Higgins et al, 2021), Twitter (Hernandez-Suarez et al, 2018; Dongo et al, 2021), Facebook (Mancosu & Vegetti, 2020). There are even manuals concerning scraping data from the web and social media and using it in analytics (Russell, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Abortion challenges both within and outside of the formal healthcare system were compounded by the financial stress felt by many during the initial stages of the pandemic. Due to the Hyde Amendment's ban on federal Medicaid funding for abortion, most women, transgender men, and other reproductive‐age people capable of pregnancy live in states without publicly subsidized coverage for abortion‐related healthcare, even though Medicaid covers prenatal and birthing care costs 30,31 . Thus, patients must pay out‐of‐pocket for both the $500–$1000 in procedural costs as well as costs related to travel, time off from work, and childcare to distant clinics involving unnecessary multiple visits 32–34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our final data set contained 168 posts spanning from March 20, 2020 until April 13, 2020. Each day garnered an average of 22 posts (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and the number of posts gradually increased over the 4 weeks, concluding on April 13, 2020. The included posts averaged of 302 words, roughly half a single-spaced page, with a range of 17 words to 5119 words (a many-paragraph story).…”
Section: Samplementioning
confidence: 99%
“…People with low income often have little flexibility in schedules and need to work every day and hour possible to earn enough to cover everyday costs such as food and housing; taking time away from work would generate less income at the same time as creating more costs for people who can afford neither. Costs for abortion were prohibitive even before the Dobbs decision (see Higgins et al, 2021a , b ), but travel estimates suggest that the distance to the closest abortion facility will increase from 25 to 122 miles, and that 26% of women will have to travel more than 200 miles to access abortion care (Myers et al, 2019 ). This has direct implications for cost increases (e.g., gas, public transportation) as well as indirect implications (e.g., hotel stays, more lost wages).…”
Section: Implications Of the Dobbs Decision For Gender And Income Ine...mentioning
confidence: 99%
“…While most of the discussion around the Dobbs decision rightly focuses on its impact on reproductive freedom, OHP researchers also should address potential impacts on healthcare personnel. Studies show that a substantial majority of healthcare providers believe that abortion services should be accessible to patients with few or no restrictions (Dodge et al, 2016 ; Schmuhl et al, 2021 ; Higgins et al, 2021a , b ). Higgins et al also found that 83% of a large sample of physician respondents expressed concerns about restrictive abortion laws making it difficult to recruit faculty and 66% reported worrying about effects on trainee recruitment.…”
Section: Impacts Of Dobbs Decision On Medical Personnelmentioning
confidence: 99%